Lembayung Senja Quality Family Village: Social Capital in Community Development Practice - Cucu Cahyati; Nunung Nurwanti; Muhammad Fedryansyah; Leo Susanto (Jurnal Pemberdayaan Masyarakat, 2026)
This study examines the role of social capital in shaping community participation within the Lembayung Senja Quality Family Village using a qualitative case study approach. It explores how a program that initially faced community resistance gradually transformed into a sustainable, community-driven initiative. The findings reveal that participation does not emerge as a precondition but rather as an outcome of evolving social capital, characterized by increased trust, expanded social networks, and the formation of collective norms. The study also identifies a shift from instrumental social capital, driven by individual interests, toward normative social capital rooted in shared values and collective responsibility. This transformation is facilitated by continuous social interaction, local leadership, and the program's relevance to community needs. These findings suggest that community-based development cannot rely solely on structural interventions; it must also prioritize strengthening social relations. However, existing studies on quality family villages largely focus on program outcomes, with limited attention to the social mechanisms underlying participation. This study addresses this gap by positioning social capital as a mediating and transformative mechanism linking policy intervention to sustained community participation.